2008
DOI: 10.1177/0022466907313451
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Learning Characteristics of Students Taking Alternate Assessments Based on Alternate Achievement Standards

Abstract: This study examined the learner characteristics of students in alternate assessments based on alternate achievement standards in three geographically and demographically different states. On the basis of the results, it can be argued that students in alternate assessments fall into at least two distinct subgroups. The first set of learners have either symbolic or emerging symbolic levels of communication, evidence social engagement, and possess at least some level of functional reading and math skills. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 11 publications
2
48
1
1
Order By: Relevance
“…Probably the most significant contribution of the present study is the interpretation of growth, an issue that has not previously been documented with empirical results along with information on test development, administration, and technical adequacy, extending the findings of previous research on this population, particularly its definition (Kearns, TowlesReeves, Kleinert, Kleinert, & Thomas, 2009;Quenemoen, 2009;Towles-Reeves, Kearns, Kleinert, & Kleinert, 2008). The real question about growth is consideration of the context of that growth.…”
Section: Findings and Interpretations In Comparing The Two Strategiessupporting
confidence: 70%
“…Probably the most significant contribution of the present study is the interpretation of growth, an issue that has not previously been documented with empirical results along with information on test development, administration, and technical adequacy, extending the findings of previous research on this population, particularly its definition (Kearns, TowlesReeves, Kleinert, Kleinert, & Thomas, 2009;Quenemoen, 2009;Towles-Reeves, Kearns, Kleinert, & Kleinert, 2008). The real question about growth is consideration of the context of that growth.…”
Section: Findings and Interpretations In Comparing The Two Strategiessupporting
confidence: 70%
“…Recently, Towles-Reeves, Kearns, Kleinert, and Kleinert (2009; see also Kearns et al, 2011) found that a significant subset of SSCD taking AA-AAS had not yet acquired the use of fully symbolic modes of communication (i.e., the use of words, signs, or other means of formal language) but were still in the emerging symbolic (e.g., communication supported by picture and/or augmentative devices or gestural prompts) or presymbolic (e.g., communication primarily through facial expressions and changes in muscle tone) stages. In addition, SSCD had very inconsistent expressive and receptive communication, had low-level engagement, and required assistance with motor skills.…”
mentioning
confidence: 99%
“…For example, several studies have reported that students with the most significant cognitive disabilities participating in the AA-AAS experience notable difficulties in expressive and receptive communication and often require augmentative/ alternative communication systems (Almond & Bechard, 2005;Kearns et al, 2011;Towles-Reeves, Kearns, Kleinert, & Kleinert, 2009). However, these indicators also accurately describe some students with orthopedic impairments; expressive and receptive language disorders are commonly observed among individuals with cerebral palsy who do not have intellectual disabilities (Pellegrino, 2002).…”
Section: Discussionmentioning
confidence: 99%